Schriften zur Dialektik und Rhetorik = Principal writings on dialectic and rhetoric : principal writings on rhetoric - Melanchthon, Philip, 1497-1560 (Melanchthon, Philip, 1497-1560. Opera omnia. Opera philosophica. 2017, 2017)
The need for a new critical edition of Philip Melanchthon's philosophical works is particularly clear in the case of his writings on rhetoric. That Melanchthon played a central role in the transformation of the ancient discipline has been well established by historians. His writings on rhetoric have proven significant sources for several academic fields, including church history, Scriptural interpretation, the history of science, and the reception of classical literature. Remarkably, two of the three principal writings have not been published in their entirety since the sixteenth century. This volume collects critical editions of the three principal writings to provide a more complete record of Melanchthon's teaching of rhetoric. It includes critical editions of De Rhetorica (1519), Institutiones Rhetoricae (1521), and Elementa Rhetorices (1531). In addition to the three principal writings, this volume collects a new edition, based on a 1911 edition by Hanns Zwicker, of Dispositiones Rhetoricae (c. 1553), a manuscript compilation of 161 model themes. Scholars will find in this volume the major sources for Melanchthon's theory and practice of rhetorical instruction.